Modern problems of linguistics and methods of teaching English - Norjon Gafurova (Proceedings of The ICECRS, 2019)
This article discusses the problem of intercultural communication, in which background knowledge plays an important role. Referring to our research, we see a solution to this problem in expanding the students' background knowledge, i.e. familiarization of students with the realities, traditions and customs of English-speaking countries. Accordingly, several components help to better master the language being studied, as a result of which a system of knowledge of a foreign language is formed, implemented and operates as a means of communication.